2017
DOI: 10.1016/j.quaint.2016.08.032
|View full text |Cite
|
Sign up to set email alerts
|

Elemental fingerprinting of Kenya Rift Valley ochre deposits for provenance studies of rock art and archaeological pigments

Abstract: The Kenya Rift Valley contains many ochre sources that are currently used by indigenous peoples for adornment, rituals, and art. Ochre pigments occur in rock art and archaeological sites spanning over 250,000 years. Chemical analysis for provenience of geological sources is the first step in the process of reconstructing provenance of archaeological artifacts for cultural heritage, archaeological, and paleoanthropological research. Development of an ochre source chemical composition database can facilitate rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 110 publications
(142 reference statements)
0
19
0
Order By: Relevance
“…Yet there is also evidence for deep continuity and resilience in tool-use traditions. Grinding-stone tools have been grinding ochre for hundreds of millennia (Zipkin et al 2016). Grinding-stones may have even been used in the processing of wild cereal grains such as sorghum as early as ca.…”
Section: Grinding-stones In the African Archaeological Recordmentioning
confidence: 99%
“…Yet there is also evidence for deep continuity and resilience in tool-use traditions. Grinding-stone tools have been grinding ochre for hundreds of millennia (Zipkin et al 2016). Grinding-stones may have even been used in the processing of wild cereal grains such as sorghum as early as ca.…”
Section: Grinding-stones In the African Archaeological Recordmentioning
confidence: 99%
“…However, statistical models employing Fe normalization plus Log 10 to reduce the variance have recently been used by some authors investigating ochre raw material procurement locations (Dayet et al, 2016; Eiselt et al, 2019; MacDonald et al, 2018; Velliky et al, 2019; Zipkin et al, 2017). Therefore, a CA was carried out using the proposed parameters for all the elements (except Fe) (Figure 9a–c) to observe whether the groupings are equivalent to those of the prior model (Figure 8a–c).…”
Section: Resultsmentioning
confidence: 99%
“…In the first cluster (Figure 8), all analyzed elements (Al 2 O 3 , SiO 2 , CaO, Ti, Fe, Ba, Bi, Cd, Cr, Co, Cu, Pb, Li, Mn, Mo, Ni, Sr, Tl, V, Zn, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Sc, and Y) were taken as variables. Furthermore, following the geochemical data treatment recently employed by some authors for ochre provenance studies (Dayet, Le Bourdonnec, Daniel, Porraz, & Texier, 2016; Eiselt et al, 2019; MacDonald, Fox, Dubreuil, Beddard, & Pidruczny, 2018; Velliky, Barbieri, Porr, Conard, & MacDonald, 2019; Zipkin et al, 2017) in the second cluster (Figure 9), the same elements (except Fe) were Fe‐normalized and subsequently log 10 transformed. The data were autoscaled before analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Mercader 2009;Radomski and Neumann 2011;Ball et al 2016). Recent progress in the elemental fingerprinting of ochre deposits in the Kenya Rift Valley (Zipkin et al 2017) also opens up the possibility of determining the origins of the ochre found on PN grinding-stones and thus of exploring patterns in wider landscape resource use. The potential remains to investigate whether different PN communities used distinct ochre sources, or manufactured their grinding-stone tools from specific lithic materials, as has previously been observed in relation to obsidian found on Elmenteitan and SPN sites in the Central Rift Valley (Merrick and Brown 1984).…”
Section: Towards An Understanding Of Tool Form and Functionmentioning
confidence: 99%